Biogeography of Phormidium autumnale (Oscillatoriales, Cyanobacteria) in western and central Spitsbergen - Strunecký, O. (Otakar); Komárek, J. (Jiří); Elster, J. (Josef) (Polish Polar Research, 2012)
Filamentous types from the order Oscillatoriales, particularly the species Phormidium autumnale, have widely diverse morphotypes, which dominate in Arctic aquatic microbial mats and wet soils. We cultivated 25 strains of Ph. autumnale from Svalbard and compared them with available strains from surrounding regions. The comparison of strains, based on 16S rDNA and 16S−23S rDNA intergenic spacer sequences, revealed the similarity of strains from Ellesmere Island, the Canadian Arctic and Abisko, Sweden with strains from Svalbard. The rate of colonization of Ph. atumnale from aquatic habitats is relatively high and we suggest geese as a main transmission vector from surrounding lands.